2022
DOI: 10.1038/s41598-022-15964-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment using 18F-FDG PET/CT as a novel predictor for early response to PD-1 blockade in non-small-cell lung cancer

Abstract: Anti-programmed death-1 (PD-1) blockade is a standard treatment for advanced non-small-cell lung cancer (NSCLC). However, no appropriate modality exists for monitoring its therapeutic response immediately after initiation. Therefore, we aimed to elucidate the clinical relevance of 18F-FDG PET/CT versus CT in predicting the response to PD-1 blockade in the early phase. This prospective study included a total of 54 NSCLC patients. 18F-FDG PET/CT was performed at 4 weeks and 9 weeks after PD-1 blockade monotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…The present study design has been previously reported [ 4 ]. This study was a multicenter prospective investigation in which eight Japanese institutions participated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study design has been previously reported [ 4 ]. This study was a multicenter prospective investigation in which eight Japanese institutions participated.…”
Section: Methodsmentioning
confidence: 99%
“…Even though many investigations have attempted to identify an optimal predictor of PD-1 blockade, the confirmation of established biomarkers has failed, aside from the expression of PD-L1 within tumor cells [ 3 ]. Therefore, we prospectively examined the prognostic significance of metabolic activity to determine whether 2-deoxy-2-[fluorine-18]-fluoro- d -glucose ( 18 F-FDG) positron emission tomography (PET) can predict the efficacy of PD-1 blockade in the early phase after its initiation [ 4 ]. It was confirmed that 18 F-FDG PET was superior to computed tomography (CT) for the detection of responders and non-responders 1 month after PD-1 blockade administration [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, non-small cell lung cancer (NSCLC) occupies 80% of lung cancer cases [ 31 ]. Recently, great progress has been made in identifying novel diagnostic and prognostic biomarkers for lung cancer, including RBR E3 ubiquitin ligase [ 32 ], prostaglandin E synthase 3 (PTGES3) [ 33 ], fibroblast activation protein (FAP) [ 34 ], checkpoint inhibitor immunotherapy targeting programmed cell death 1 (PD1), and programmed death ligand 1 (PDL1) pathways [ 35 , 36 ]. However, the 5-year overall survival rate of lung cancer remains low among all the cancer types, and its high mortality can be ascribed to the fact that most patients are diagnosed at an advanced stage and the treatment options are thereby limited, with a 5-year survival rate of only 4% [ 37 ].…”
Section: Mirnas and Cancer Diagnosis And Prognosismentioning
confidence: 99%